A Semiotic Analysis Of “Marry Your Daughter” Song By Brian Mcknight Based On Ferdinand De Saussure’s Theory - Indah Juniasari T.; Nadila Aulia Ashyurin; Osy Benu Ismail; Wulan Widya Istiyana; Yati Kurniati; Mayang Pipit (International journal of technology and education research, 2026)
This study presents a semiotic analysis of Brian McKnight’s song “Marry Your Daughter” (2008), drawing on Ferdinand de Saussure’s theory of linguistic signs. The primary aim is to identify and interpret the signs, signifiers, and signifieds embedded in the song lyrics, and to examine how these linguistic elements construct concepts of love, commitment, family values, and marriage. Employing a qualitative descriptive approach, the analysis applies Saussure’s dyadic model of the sign—consisting of signifier (the sound-image or word form) and signified (the conceptual meaning)—to six key lyrical phrases selected purposively from the song text. The findings reveal that McKnight’s lyrics deploy a network of culturally loaded signs that convey not only romantic sentiment but also socially shared values of respect, faithfulness, and familial approval. Words and phrases such as “love of my life,” “promise to be true,” and “marry your daughter” function as powerful semiotic markers that reflect broader cultural and emotional ideals surrounding the institution of marriage. This study demonstrates that song lyrics constitute a rich semiotic text through which deeply held cultural values are encoded and communicated, and it affirms the relevance of Saussurean semiotics as an analytical framework in language and literature education.